The Dark Side of Organizational Change: The Moderating Role of Political Behavior and Organizational Cynicism - Miranda, Sandra (2015)
Workplace aggression is a factor that shapes the interaction between individuals and their work environment and produces many undesirable outcomes, sometimes introducing heavy costs for organizations. Only through a comprehensive understanding of the genesis of workplace aggression is possible to develop strategies and interventions to minimize its nefarious effects. The existent body of knowledge has already identified several individual, situational and contextual antecedents of workplace aggression, although this is a research area where significant gaps occur and many issues were still not addressed Dupré and Barling (2006). According to Baron and Neuman (1998) one of these predictors is organizational change, since certain changes in the work environment (e.g., changes in management) can lead to increased aggression. This paper intends to contribute to workplace aggression research by studying its relationship with organizational change, considering a moderating role of political behaviors and organizational cynicism (Ammeter et al., 2002, Ferris et al., 2002). The literature review suggests that mediators and moderators that intervene in the relationships between workplace aggression and its antecedents are understudied topics. James (2005) sustains that organizational politics is related to cynicism and the empirical research of Miranda (2008) has identified leadership political behavior as an antecedent of cynicism but these two variables were not yet investigated regarding their relationship with workplace aggression. This investigation was operationalized using several scales including the Organizational Change Questionnaire-climate of change, processes, and readiness (Bouckenooghe, Devos and Broeck, 2009), a Workplace Aggression Scale (Vicente and D’Oliveira, 2008, 2009, 2010), an Organizational Cynicism Scale (Wanous, Reichers and Austin, 1994) and a Political Behavior Questionnaire (Yukl and Falbe, 1990). Participants representing a wide variety of jobs across many organizations were surveyed. The results of the study and its implications will be presented and discussed. This study contribution is also discussed in what concerns organizational change practices in organizations.